STUDI FENOMENOLOGI : PENGALAMAN KESEPIAN PADA LANSIA YANG TINGGAL DIRUMAH SEORANG DIRI DI DESA TUNGGUL WULUNG – PANDAAN - Fransiska Imavike***, Evy Aristawati* Retty Ratnawati** (The Indonesian Journal of Health Science, 2015)
Loneliness experienced on the elderly bring meaning and different expectations. Elderly sometimes not able to actively interact with their environment and adapt more slowly because of the conditions they experience so that researchers interested in using a qualitative approach to the design of phenomenology. According Streubert & Carpenter (1999) The study design used is qualitative interpretative phenomenological approach .indepth interviews using semistructured questions involving four elderly people who experience loneliness and in daily living at home alone. Data were collected and analyzed using thematic analysis approach based Braun & Clark. This study resulted in five themes namely the feeling of loneliness, self-assessment, emotional, situational, quality of life, the pattern of life and views on illness and death from the seventh Where the theme converging on the main themes, namely the meaning of life alive. The results of the overall interview participants showed one of things that support the achievement of the meaning of life in the elderly living at home alone is a change in the spiritual aspect, in this aspect there was an increase in integrated religion and belief in life where the elderly increasingly mature in their religious life. Spiritual terms generally expect condition, elderly healthy physical, longevity, zest for life, remain authoritative and face death in tranquility with spiritual provisions that they have.